On the in-situ aqueous stability of an Mg-Li-(Al-Y-Zr) alloy: Role of Li. (March 2020) - Yan, Y.M.; Maltseva, A.; Zhou, P.; Li, X.J.; Zeng, Z.R.; Gharbi, O.; Ogle, K.; La Haye, M.; Vaudescal, M.; Esmaily, M.; Birbilis, N.; Volovitch, P.
Graphical abstract: Highlights: Li dissolves from Mg-Li-(Y-Al-Zr) while Mg forms oxygen deficient oxide film (MgO1-x ). Li + doping of MgO1-x slows down transformation MgO→Mg(OH)2 . Li2 [Al2 (OH)6 ]2 ·CO3 ·nH2 O (LDH), LiAlO2, Y2 O3 and Mg(OH)2 grow locally on cathodes. Cathodic activity is expected to be weakened on Li-doped MgO and LDH. Li2 CO3 formed on Mg-Li-(Y-Al-Zr) in air exposure can be a reservoir of Li + . Abstract: The aqueous stability of a corrosion resistant Mg-Li(-Al-Y-Zr)-alloy was investigated by combining in-situ confocal Raman Microscopy, Atomic Emission SpectroElectroChemistry, ex-situ Photoluminiscence Spectroscopy, Auger Electron Spectroscopy and Glow Discharge Optical Emission Spectroscopy. Li and Mg dissolved from visually intact anodic areas, leaving a Li-depleted metallic layer under approximately 100 nm thick Li-doped MgO. The transformation MgO→Mg(OH)2 was inhibited. Li2 [Al2 (OH)6 ]2 ·CO3 ·nH2 O, LiAlO2, Y2 O3 and Mg(OH)2 accumulated locally around active cathodic sites. New corrosion mechanism is proposed, which associates the improved corrosion resistance of Mg-Li alloys with an enhanced chemical stability and modified catalytic activity of MgO in presence of Li + .